Large-area flexible perovskite solar cell and preparation method and application thereof
By using UV glue of specific components to separate the flexible substrate and the rigid substrate, the problem of perovskite damage during the separation process of flexible perovskite solar cells is solved, and excellent photoconversion of large-area flexible perovskite solar cells is achieved. Efficiency and stability reduce costs, and ensure high transmittance of the flexible substrate and high temperature resistance and waterproof performance of UV glue.
Patent Information
- Application Number
- CN202411363264.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
When existing large-area flexible perovskite solar cells separate flexible substrates from rigid substrates, they are prone to perovskite damage, and have poor photoelectric performance, making it difficult to achieve excellent photoconversion efficiency and stability.
UV glue with specific components, including polyester organics, epoxy acrylates, polyolefin-thiol systems and photoinitiators, separate the flexible substrate from the rigid substrate through adhesion and photolysis technology, avoiding heating and rolling, ensuring Perovskite integrity and no UV glue residue after separation.
The excellent light conversion efficiency and stability of large-area flexible perovskite solar cells are achieved, which reduces costs, and ensures the high transmittance of the flexible substrate and the high temperature and waterproof performance of UV glue.
Smart Images

Figure CN119255681A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of photovoltaic technology, and specifically relates to a large-area flexible perovskite solar cell and a preparation method and application thereof. Background Art
[0002] Flexible perovskite solar cells have the characteristics of high efficiency, light weight, and bendability. The existing large-area battery preparation process widely uses a flexible substrate attached to a rigid glass surface. Perovskite has extremely high requirements for flexibility and flatness, so the separation of the flexible substrate and the rigid glass has extremely high requirements. However, many patents simplify the process of separating the flexible substrate from the rigid substrate, resulting in the photoelectric performance of the flexible perovskite solar cells being significantly worse than that of the rigid perovskite solar cells.
[0003] One of the technical difficulties in preparing large-area flexible perovskite solar cells is the separation of flexibility and rigidity. If the separation is done by heating, the perovskite cannot withstand overheating, and if the separation is done by winding, the crystallized perovskite will be damaged.
[0004] Therefore, there is an urgent need to provide a method for separating a flexible substrate from a rigid substrate so that the perovskite is not damaged after the flexible substrate is separated, and the large-area flexible perovskite solar cell obtained has excellent light conversion efficiency. Summary of the invention
[0005] In view of the deficiencies of the prior art, the purpose of the present invention is to provide a large-area flexible perovskite solar cell and a preparation method and application thereof. The present invention introduces a UV glue with specific components, which has excellent high temperature resistance, adhesion and waterproof properties, so that the flexible substrate can be smoothly pasted on the rigid substrate, and when the two are separated, not only is there no UV glue residue on the flexible substrate, but also the separation process does not require heating or rolling, and will not cause damage to the perovskite. Based on this, the large-area flexible perovskite solar cell obtained has excellent light conversion efficiency and stability.
[0006] In order to achieve the purpose of the invention, the present invention adopts the following technical solutions:
[0007] In a first aspect, the present invention provides a method for preparing a large-area flexible perovskite solar cell, the preparation method comprising the following steps:
[0008] (1) UV glue is coated on one side surface of a flexible substrate, and then the flexible substrate is attached to a rigid substrate to achieve adhesion through the UV glue.
[0009] (2) depositing a conductive layer, a first charge transport layer, a perovskite layer, a second charge transport layer and an electrode layer in sequence on a surface of the flexible substrate away from the rigid substrate.
[0010] (3) Photolyzing the UV glue, and providing a layer of polymer film on the electrode layer, so that the polymer film and the flexible substrate are attached to each other on all sides, and then performing sealing hot melting to complete the packaging, thereby obtaining the large-area flexible perovskite solar cell.
[0011] Wherein, the UV glue comprises polyester organic matter, epoxy acrylate, polyolefin-thiol system and photoinitiator.
[0012] The present invention introduces a UV glue with specific components, which has excellent high temperature resistance, adhesion and waterproof properties, so that the flexible substrate can be smoothly pasted on the rigid substrate. When the two are separated, not only is there no UV glue residue on the flexible substrate, but the separation process does not require heating or rolling, and will not cause damage to the perovskite. Based on this, the large-area flexible perovskite solar cell obtained has excellent light conversion efficiency and stability.
[0013] The UV glue introduced in the present invention has the following advantages: 1) It can withstand high temperature cyclic baking above 600°C without losing its viscosity (if it loses viscosity, the flexible substrate will be warped, causing the internal structure of the perovskite to be destroyed). 2) It can achieve good waterproof performance while being able to withstand high temperature baking. 3) It has excellent strong acid resistance.
[0014] It should be noted that the effective area of the large-area flexible perovskite solar cell provided by the present invention can be 686cm 2 .
[0015] It should be noted that the polymer film is directly attached to the surface of the electrode layer.
[0016] Preferably, the UV glue comprises the following components in percentage by mass:
[0017] Polyester organic matter 45-55%, for example, it can be 45%, 46%, 47%, 48%, 49%, 50%, 51%, 52%, 53%, 54% or 55%, etc., polyolefin-thiol system 5-15%, for example, it can be 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%, etc., photoinitiator 2-10%, for example, it can be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and the balance is epoxy acrylate.
[0018] In the present invention, the UV glue prepared by each component within the above range has excellent high temperature resistance and adhesion, and can achieve sufficient photolysis when separating the flexible substrate and the rigid substrate, without residue, so that the separated flexible substrate has a high transmittance. If the mass fraction of the polyester organic matter is too small, the curing speed may slow down, and its insufficient content may lead to insufficient reaction, and the mechanical properties and durability of the UV glue may decrease, including hardness, strength and wear resistance, and the chemical resistance and environmental resistance of the UV glue may weaken, and the viscosity of the glue may decrease, affecting its coating performance and bonding ability. If the mass fraction of the polyester organic matter is too large, the curing speed may be too fast, resulting in a narrowing of the operating time window, which is not conducive to construction, and the glue may become too hard and brittle, resulting in a decrease in flexibility and impact resistance, and may also cause an increase in viscosity, making it difficult to apply the UV glue evenly, especially in small gaps or thin layers, and finally, the cost increases. If the mass fraction of the polyolefin-thiol system is too small, the crosslinking density may be reduced, affecting the mechanical properties and chemical resistance of the UV glue. Secondly, the curing speed may be slowed down because the thiol group helps to accelerate the curing process. Secondly, the bonding strength may decrease because the crosslinking network is insufficient, affecting the bonding interface, and the heat resistance and durability of the UV glue may be weakened. If the mass fraction of the polyolefin-thiol system is too large, the curing speed may be too fast, making the construction more difficult. Secondly, the crosslinking density may be too high, causing the glue to become brittle, and the flexibility and impact resistance to decrease, and the viscosity may increase significantly, affecting the fluidity and coating performance of the glue.
[0019] Preferably, the polyester organic matter includes any one of unsaturated polyester, polyacrylate or polyurethane acrylate or a combination of at least two of them, preferably a combination of unsaturated polyester, polyacrylate and polyurethane acrylate.
[0020] In the present invention, the combination of unsaturated polyester, polyacrylate and polyurethane acrylate is used, which is more conducive to achieving that the UV glue does not remain on the surface of the substrate during photolysis.
[0021] Preferably, based on the mass of the polyester organic matter, the mass fraction of the unsaturated polyester is 10-50%, for example, 10%, 20%, 30%, 40% or 50%, etc., the mass fraction of the polyacrylate is 20-60%, for example, 20%, 30%, 40%, 50% or 60%, etc., and the mass fraction of the polyurethane acrylate is 10-40%, for example, 10%, 20%, 30% or 40%, etc.
[0022] Preferably, the photoinitiator includes any one of benzoin derivatives, dibenzoyl derivatives, α-carboxy ketone compounds, α-amino ketone compounds, phosphine oxide compounds, benzophenone or thioxanthone, or a combination of at least two thereof.
[0023] Preferably, the coating method in step (1) includes slit coating or spin coating.
[0024] Preferably, the material of the flexible substrate in step (1) includes any one of PET (polyethylene terephthalate), PEN (polyethylene naphthalate) or PI (polyimide).
[0025] Preferably, the rigid substrate in step (1) comprises a glass substrate.
[0026] Preferably, the conductive layer in step (2) comprises a FTO (fluorine-doped tin oxide) layer.
[0027] Preferably, in step (2), the charges transported by the first charge transport layer and the second charge transport layer are of opposite electrical properties.
[0028] Preferably, in step (2), the first charge transport layer is a hole transport layer, and the hole transport layer comprises a nickel oxide layer.
[0029] It should be noted that the present invention does not limit the deposition method of the hole transport layer. Exemplary method thereof may be physical vapor deposition, such as magnetron sputtering.
[0030] Preferably, in step (2), the second charge transport layer is an electron transport layer, and the electron transport layer comprises a tin oxide layer and / or a C 60 layer.
[0031] It should be noted that the present invention does not limit the deposition method of the electron transport layer. Exemplary methods include thermal evaporation, spin coating, and the like.
[0032] Preferably, the perovskite layer in step (2) comprises any one of an organic perovskite layer, an organic-inorganic hybrid perovskite layer or an inorganic perovskite layer.
[0033] It should be noted that the general chemical formula of the perovskite layer is ABX3, wherein A is any one of formamidinium ion, methylamine ion or cesium ion or a combination of at least two thereof, B is lead ion and / or tin ion, and X is any one of chloride ion, bromide ion or iodide ion or a combination of at least two thereof.
[0034] It should be noted that the present invention does not limit the deposition method of the perovskite layer, and illustratively, it may be a spin coating method, a slit coating method, etc.
[0035] Preferably, the electrode layer in step (2) is a metal electrode layer, for example, a gold electrode layer or a silver electrode layer.
[0036] It should be noted that the present invention does not limit the deposition method of the electrode layer. Exemplarily, it may be a physical vapor deposition method, such as thermal evaporation method.
[0037] Preferably, the material of the polymer film in step (3) is the same as the material of the flexible substrate.
[0038] Preferably, the specific steps of sequentially depositing the conductive layer, the first charge transport layer, the perovskite layer, the second charge transport layer and the electrode layer in step (2) include:
[0039] (a) depositing a conductive layer on a surface of a flexible substrate away from the rigid substrate, and then performing a first laser scribing on a surface of the conductive layer away from the flexible substrate to form a plurality of evenly spaced first scribing grooves; wherein the conductive layer is removed in the first scribing grooves.
[0040] (b) depositing a first charge transport layer, a perovskite layer, and a second charge transport layer in sequence on the surface of the conductive layer after the first laser scribing, and then performing a second laser scribing on the surface of the second charge transport layer away from the flexible substrate to form a plurality of evenly spaced second grooves; wherein the first charge transport layer, the perovskite layer, and the second charge transport layer are removed in the second grooves, and the second grooves are located on one side of the first grooves and are spaced apart from the first grooves.
[0041] (c) depositing an electrode layer on the surface of the second charge transport layer after the second laser scribing, and then performing a third laser scribing on the surface of the electrode layer away from the flexible substrate to form a plurality of evenly spaced third grooves; wherein the first charge transport layer, the perovskite layer, the second charge transport layer and the electrode layer are removed in the third grooves, the third grooves are located on one side of the second grooves and are spaced apart from the second grooves, and the second grooves are located between the first grooves and the third grooves.
[0042] Preferably, the specific steps of the sealed hot melt in step (3) include:
[0043] First, the polymer film and the flexible substrate are heat-fused in three directions after being bonded around each other. Then, the openings that have not been heat-fused are vacuumed, inert gas is passed, and vacuumed again in sequence, and then the openings are heat-fused.
[0044] The present invention adopts the above method to perform sealing hot melting to reduce water and oxygen in the packaged device, which is beneficial to slow down the decomposition of perovskite inside the device, improve the stability of large-area perovskite solar cells, and perfectly solve the problem of being unable to seal at high temperature in a designated area.
[0045] Preferably, the preparation method comprises the following steps:
[0046] (1) Preparation of UV glue:
[0047] The UV glue is obtained by mixing polyacrylate, polyurethane acrylate, unsaturated polyester, epoxy acrylate, polyolefin-thiol system and photoinitiator; wherein the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 45-55%, the proportion of polyolefin-thiol system is 5-15%, the proportion of photoinitiator is 2-10%, and the balance is epoxy acrylate.
[0048] (2) UV glue is coated on one side of the flexible substrate by a slit coating method, and then the flexible substrate is attached to the glass substrate to achieve adhesion by UV glue.
[0049] (3) depositing an FTO layer on the surface of the flexible substrate away from the rigid substrate, and then performing a first laser scribing on the surface of the FTO layer away from the flexible substrate to form a plurality of evenly spaced first grooves; wherein the FTO layer is removed in the first grooves; the first laser scribing uses a laser with a wavelength of 1064 nm, and the laser is incident perpendicular to the surface of the FTO layer; and the interval between adjacent first grooves is 25-35 μm (for example, it can be 25 μm, 30 μm or 35 μm, etc.).
[0050] (4) After the first laser scribing, a hole transport layer with a thickness of 15-25 nm (it should be noted that this thickness refers to the thickness of the layer outside the scribing groove, and the same applies below), a perovskite layer with a thickness of 500-600 nm (for example, it can be 500 nm, 520 nm, 540 nm, 560 nm, 580 nm or 600 nm, etc.), and an electron transport layer with a thickness of 30-40 nm (for example, it can be 30 nm, 32 nm, 34 nm, 36 nm, 38 nm or 40 nm, etc.) are sequentially deposited on the surface of the FTO layer after the first laser scribing, and then a second laser scribing is performed on the surface of the electron transport layer away from the flexible substrate. , forming a plurality of evenly spaced second grooves; wherein, the hole transport layer, the perovskite layer and the electron transport layer are removed in the second groove, the second groove is located on one side of the first groove, and there is a gap between the second groove and the first groove; the second laser scribing uses a laser with a wavelength of 532nm, and the laser is incident perpendicular to the surface of the electron transport layer; the interval between adjacent second grooves is 45-55μm (for example, it can be 45μm, 50μm or 55μm, etc.), and the interval between the second groove and the first groove is 10-20μm (for example, it can be 10μm, 15μm or 20μm, etc.).
[0051] (5) a metal electrode layer with a thickness of 80-120 nm (for example, 80 nm, 100 nm or 120 nm) is deposited on the surface of the electron transport layer after the second laser scribing, and then a third laser scribing is performed on the surface of the metal electrode layer on a side away from the flexible substrate to form a plurality of evenly spaced third grooves; wherein the hole transport layer, the perovskite layer, the electron transport layer and the metal electrode layer are removed in the third grooves, the third grooves are located on one side of the second grooves, and there is a gap between the third grooves and the second grooves, and the second grooves are located between the first grooves and the third grooves; the third laser scribing uses a laser with a wavelength of 355 nm, and the laser is incident perpendicular to the surface of the metal electrode layer; the interval between adjacent third grooves is 35-45 μm (for example, 35 μm, 40 μm or 45 μm), and the interval between the second grooves and the third grooves is 25-35 μm (for example, 25 μm, 30 μm or 35 μm).
[0052] (6) Using a UV decomposition machine, the UV glue is photolyzed to make the UV glue lose its stickiness and separate from the flexible substrate. Then, a layer of polymer film is disposed on the metal electrode layer, so that the polymer film and the flexible substrate are bonded to each other on all sides, and then sealed by hot melting. That is, the polymer film and the flexible substrate are first hot melted in three directions after being bonded to each other on all sides. Then, vacuuming, passing inert gas, and vacuuming are performed in sequence through the opening that has not been hot melted. Subsequently, the opening is hot melted and sealed to complete the packaging, thereby obtaining the large-area flexible perovskite solar cell.
[0053] In a second aspect, the present invention provides a large-area flexible perovskite solar cell, which is prepared by the preparation method described in the first aspect.
[0054] In a third aspect, the present invention provides a photovoltaic module, comprising the large-area flexible perovskite solar cell as described in the second aspect.
[0055] The numerical range described in the present invention not only includes the point values listed above, but also includes any point values between the above numerical ranges that are not listed. Due to space limitations and for the sake of simplicity, the present invention no longer exhaustively lists the specific point values included in the range.
[0056] Compared with the prior art, the present invention has the following beneficial effects:
[0057] (1) The present invention introduces a UV glue with specific components, which has excellent high temperature resistance, adhesion and waterproof properties, so that the flexible substrate can be smoothly pasted on the rigid substrate. When the two are separated, not only is there no UV glue residue on the flexible substrate, but the separation process does not require heating or rolling, and will not cause damage to the perovskite. Based on this, the large-area flexible perovskite solar cell obtained has excellent light conversion efficiency and stability.
[0058] (2) In the preparation method provided by the present invention, after the flexible substrate and the rigid substrate are separated, the rigid substrate can be recycled, which is beneficial to reducing costs. BRIEF DESCRIPTION OF THE DRAWINGS
[0059] Figure 1 These are transmittance curves of the flexible substrates provided in Example 1 and Comparative Example 1 of the present invention after debonding. DETAILED DESCRIPTION
[0060] The technical solution of the present invention is further described below by specific implementation methods. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0061] Example 1
[0062] This embodiment provides a method for preparing a large-area flexible perovskite solar cell, the preparation method comprising the following steps:
[0063] (1) Preparation of UV glue:
[0064] The UV glue is obtained by mixing polyacrylate, polyurethane acrylate, unsaturated polyester, epoxy acrylate, polyolefin-thiol system and photoinitiator; wherein the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 50%, the proportion of polyolefin-thiol system is 10%, the proportion of photoinitiator is 6%, and the balance is epoxy acrylate; wherein the photoinitiator is a benzoin derivative.
[0065] (2) UV glue is coated on one side surface of a 300 mm×300 mm flexible substrate by a slit coating method, and then the flexible substrate is attached to a glass substrate by UV glue and assisted by mechanical pressing.
[0066] Wherein, the material of the flexible substrate is PET.
[0067] (3) depositing an FTO layer on a surface of the flexible substrate away from the rigid substrate, and then performing a first laser scribing on a surface of the FTO layer away from the flexible substrate to form a plurality of evenly spaced first grooves; wherein the FTO layer is removed in the first grooves; the first laser scribing uses a laser with a wavelength of 1064 nm, and the laser is incident perpendicular to the surface of the FTO layer; and the interval between adjacent first grooves is 30 μm.
[0068] (4) After the first laser scribing, a nickel oxide layer with a thickness of 20 nm is deposited on the surface of the FTO layer by magnetron sputtering, and then a layer with a thickness of 550 nm and a chemical formula of FA is deposited by slit coating. 0.7 MA 0.3 The perovskite layer of PbI3 was then deposited by thermal evaporation with a thickness of 20 nm. 60 A tin oxide layer with a thickness of 20 nm is deposited by ALD, and then a second laser scribing is performed on a surface of the tin oxide layer away from the flexible substrate to form a plurality of evenly spaced second grooves; wherein the nickel oxide layer, the perovskite layer, and the C 60 The layer and the tin oxide layer are removed, the second groove is located on one side of the first groove, and there is a gap between the second groove and the first groove; the second laser scribing uses a laser with a wavelength of 532nm, and the laser is incident perpendicular to the surface of the tin oxide layer; the interval between adjacent second grooves is 50μm, and the interval between the second groove and the first groove is 15μm.
[0069] (5) depositing a silver electrode layer with a thickness of 100 nm on the surface of the tin oxide layer after the second laser scribing, and then performing a third laser scribing on the surface of the silver electrode layer away from the flexible substrate to form a plurality of evenly spaced third scribing grooves; wherein the nickel oxide layer, the perovskite layer, and the C 60 The third groove is located on one side of the second groove and has a gap with the second groove, and the second groove is located between the first groove and the third groove; the third laser scribing adopts a laser with a wavelength of 355nm, and the laser is incident perpendicular to the surface of the metal electrode layer; the gap between adjacent third grooves is 40μm, and the gap between the second groove and the third groove is 30μm.
[0070] (6) Using a UV decomposition machine, the UV glue is photolyzed to make the UV glue lose its stickiness and separate from the flexible substrate. Then, a layer of PET film is arranged on the silver electrode layer, so that the PET film and the flexible substrate are bonded to each other on all sides, and then sealed by hot melting. That is, the polymer film and the flexible substrate are firstly hot melted in three directions after being bonded to each other on all sides. Then, vacuuming, nitrogen passing and vacuuming are sequentially performed through the opening that has not been hot melted. Then, the opening is hot melt sealed to complete the packaging, and the large-area flexible perovskite solar cell is obtained.
[0071] Example 2
[0072] This embodiment provides a method for preparing a large-area flexible perovskite solar cell, the preparation method comprising the following steps:
[0073] (1) Preparation of UV glue:
[0074] The UV glue is obtained by mixing polyacrylate, polyurethane acrylate, unsaturated polyester, epoxy acrylate, polyolefin-thiol system and photoinitiator; wherein the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 45%, the proportion of polyolefin-thiol system is 15%, the proportion of photoinitiator is 10%, and the balance is epoxy acrylate; wherein the photoinitiator is a dibenzoyl derivative.
[0075] (2) UV glue is coated on one side surface of a 300 mm×300 mm flexible substrate by a slit coating method, and then the flexible substrate is attached to a glass substrate by UV glue and assisted by mechanical pressing.
[0076] Wherein, the material of the flexible substrate is PET.
[0077] (3) depositing an FTO layer on a surface of the flexible substrate away from the rigid substrate, and then performing a first laser scribing on a surface of the FTO layer away from the flexible substrate to form a plurality of evenly spaced first grooves; wherein the FTO layer is removed in the first grooves; the first laser scribing uses a laser with a wavelength of 1064 nm, and the laser is incident perpendicular to the surface of the FTO layer; and the interval between adjacent first grooves is 30 μm.
[0078] (4) After the first laser scribing, a nickel oxide layer with a thickness of 20 nm is deposited on the surface of the FTO layer by magnetron sputtering, and then a layer with a thickness of 550 nm and a chemical formula of FA is deposited by slit coating. 0.7 MA 0.3 The perovskite layer of PbI3 was then deposited by thermal evaporation with a thickness of 20 nm. 60A layer is formed by depositing a tin oxide layer with a thickness of 15 nm by ALD, and then a second laser scribing is performed on a surface of the tin oxide layer away from the flexible substrate to form a plurality of evenly spaced second scribing grooves; wherein the nickel oxide layer, the perovskite layer, and the C 60 The layer and the tin oxide layer are removed, the second groove is located on one side of the first groove, and there is a gap between the second groove and the first groove; the second laser scribing uses a laser with a wavelength of 532nm, and the laser is incident perpendicular to the surface of the tin oxide layer; the interval between adjacent second grooves is 50μm, and the interval between the second groove and the first groove is 15μm.
[0079] (5) depositing a silver electrode layer with a thickness of 100 nm on the surface of the tin oxide layer after the second laser scribing, and then performing a third laser scribing on the surface of the silver electrode layer away from the flexible substrate to form a plurality of evenly spaced third scribing grooves; wherein the nickel oxide layer, the perovskite layer, and the C 60 The third groove is located on one side of the second groove and has a gap with the second groove, and the second groove is located between the first groove and the third groove; the third laser scribing adopts a laser with a wavelength of 355nm, and the laser is incident perpendicular to the surface of the metal electrode layer; the gap between adjacent third grooves is 40μm, and the gap between the second groove and the third groove is 30μm.
[0080] (6) Using a UV decomposition machine, the UV glue is photolyzed to make the UV glue lose its stickiness and separate from the flexible substrate. Then, a layer of PET film is arranged on the silver electrode layer, so that the PET film and the flexible substrate are bonded to each other on all sides, and then sealed by hot melting. That is, the polymer film and the flexible substrate are firstly hot melted in three directions after being bonded to each other on all sides. Then, vacuuming, nitrogen passing and vacuuming are sequentially performed through the opening that has not been hot melted. Then, the opening is hot melt sealed to complete the packaging, and the large-area flexible perovskite solar cell is obtained.
[0081] Example 3
[0082] This embodiment provides a method for preparing a large-area flexible perovskite solar cell, the preparation method comprising the following steps:
[0083] (1) Preparation of UV glue:
[0084] Polyacrylate, polyurethane acrylate, unsaturated polyester, epoxy acrylate, polyolefin-thiol system and photoinitiator are mixed to obtain the UV glue; wherein the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 55%, the proportion of polyolefin-thiol system is 5%, the proportion of photoinitiator is 2%, and the balance is epoxy acrylate; wherein the photoinitiator is benzophenone.
[0085] (2) UV glue is coated on one side surface of a 300 mm×300 mm flexible substrate by a slit coating method, and then the flexible substrate is attached to a glass substrate by UV glue and assisted by mechanical pressing.
[0086] Wherein, the material of the flexible substrate is PET.
[0087] (3) depositing an FTO layer on a surface of the flexible substrate away from the rigid substrate, and then performing a first laser scribing on a surface of the FTO layer away from the flexible substrate to form a plurality of evenly spaced first grooves; wherein the FTO layer is removed in the first grooves; the first laser scribing uses a laser with a wavelength of 1064 nm, and the laser is incident perpendicular to the surface of the FTO layer; and the interval between adjacent first grooves is 30 μm.
[0088] (4) After the first laser scribing, a nickel oxide layer with a thickness of 20 nm is deposited on the surface of the FTO layer by magnetron sputtering, and then a layer with a thickness of 550 nm and a chemical formula of FA is deposited by slit coating. 0.7 MA 0.3 The perovskite layer of PbI3 was then deposited by thermal evaporation with a thickness of 20 nm. 60 A layer is formed by depositing a tin oxide layer with a thickness of 15 nm by ALD, and then a second laser scribing is performed on a surface of the tin oxide layer away from the flexible substrate to form a plurality of evenly spaced second scribing grooves; wherein the nickel oxide layer, the perovskite layer, and the C 60 The layer and the tin oxide layer are removed, the second groove is located on one side of the first groove, and there is a gap between the second groove and the first groove; the second laser scribing uses a laser with a wavelength of 532nm, and the laser is incident perpendicular to the surface of the tin oxide layer; the interval between adjacent second grooves is 50μm, and the interval between the second groove and the first groove is 15μm.
[0089] (5) depositing a silver electrode layer on the surface of the tin oxide layer after the second laser scribing, and then performing a third laser scribing on the surface of the silver electrode layer away from the flexible substrate to form a plurality of evenly spaced third scribing grooves; wherein the nickel oxide layer, the perovskite layer, and the C 60The third groove is located on one side of the second groove and has a gap with the second groove, and the second groove is located between the first groove and the third groove; the third laser scribing adopts a laser with a wavelength of 355nm, and the laser is incident perpendicular to the surface of the metal electrode layer; the gap between adjacent third grooves is 40μm, and the gap between the second groove and the third groove is 30μm.
[0090] (6) Using a UV decomposition machine, the UV glue is photolyzed to make the UV glue lose its stickiness and separate from the flexible substrate. Then, a layer of PET film is arranged on the silver electrode layer, so that the PET film and the flexible substrate are bonded to each other on all sides, and then sealed by hot melting. That is, the polymer film and the flexible substrate are firstly hot melted in three directions after being bonded to each other on all sides. Then, vacuuming, nitrogen passing and vacuuming are sequentially performed through the opening that has not been hot melted. Then, the opening is hot melt sealed to complete the packaging, and the large-area flexible perovskite solar cell is obtained.
[0091] Example 4
[0092] The difference between this embodiment and embodiment 1 is that the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 40%.
[0093] The rest of the preparation methods and parameters were the same as those in Example 1.
[0094] Example 5
[0095] The difference between this embodiment and embodiment 1 is that the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 60%.
[0096] The rest of the preparation methods and parameters were the same as those in Example 1.
[0097] Example 6
[0098] The difference between this embodiment and embodiment 1 is that the proportion of the polyolefin-thiol system is 1%.
[0099] The rest of the preparation methods and parameters were the same as those in Example 1.
[0100] Example 7
[0101] The difference between this embodiment and embodiment 1 is that the proportion of the polyolefin-thiol system is 20%.
[0102] The rest of the preparation methods and parameters were the same as those in Example 1.
[0103] Example 8
[0104] The difference between this embodiment and embodiment 1 is that no unsaturated polyester is added to the UV glue described in step (1).
[0105] The rest of the preparation methods and parameters were the same as those in Example 1.
[0106] Comparative Example 1
[0107] The difference between this comparative example and Example 1 is that step (1) is not performed, and in step (2), the UV glue is replaced by double-sided tape, and a protective film made of a polymer material is provided on the surface of the side where the flexible substrate and the glass substrate are attached.
[0108] The rest of the preparation methods and parameters were the same as those in Example 1.
[0109] Figure 1 The transmittance curves of the flexible substrates provided in Example 1 and the comparative example after debonding are shown. It can be seen from the figure that the flexible substrate provided by the present invention has a high transmittance, indicating that the UV glue provided by the present invention leaves no residue on the flexible substrate after photolysis, while the double-sided adhesive provided in Comparative Example 1 leaves more residue after debonding.
[0110] Comparative Example 2
[0111] The difference between this comparative example and Example 1 is that no polyolefin-thiol system is added to the UV glue described in step (1).
[0112] The rest of the preparation methods and parameters were the same as those in Example 1.
[0113] Comparative Example 3
[0114] The difference between this comparative example and Example 1 is that steps (1) and (2) are not performed, but steps (3) to (6) are performed sequentially on the glass substrate.
[0115] The rest of the preparation methods and parameters were the same as those in Example 1.
[0116] Performance Testing
[0117] The large-area flexible perovskite solar cells provided in the above embodiments and comparative examples were tested for photoelectric performance, and the testing method was as follows:
[0118] A solar simulator was used to emit a standard sunlight (spectrum AM1.5G, effective area 686cm 2 , incident power 100mW / cm 2 , temperature 25℃).
[0119] The test results are shown in Table 1.
[0120] Table 1
[0121]
[0122]
[0123] analyze:
[0124] As can be seen from the above table, the present invention introduces a UV glue with specific components, which has excellent high temperature resistance, adhesion and waterproof properties, so that the flexible substrate can be smoothly pasted on the rigid substrate, and when the two are separated, not only is there no UV glue residue on the flexible substrate, but the separation process does not require heating or rolling, and will not cause damage to the perovskite. Based on this, the large-area flexible perovskite solar cell obtained has excellent light conversion efficiency.
[0125] It can be seen from Examples 1 and 4-5 that if the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is too low, the curing speed is slow, the viscosity decreases, and the substrate is uneven. The curing depth is limited, and part of the glue is not melted, resulting in an unclean substrate. The viscosity of the system will also decrease, causing the UV glue to hang on the edge, so that the uniformity is uneven during coating, resulting in a lower filling factor of the battery and a decrease in efficiency. If the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is too high, the viscosity of the glue increases, making the coating uneven, the coating becomes more difficult, the curing speed is too fast, the shrinkage rate increases, and there is a risk of tearing the entire film during dissociation. The heat resistance will also decrease accordingly. In addition, there is glue residue during dissociation, which affects the incidence of light, reduces the transmittance of the flexible substrate, reduces the current, and affects the battery efficiency.
[0126] From Examples 1 and 6-7, it can be seen that if the proportion of the polyolefin-thiol system is too low, the viscosity decreases, and there is a risk of falling off during the operation; the coating uniformity is low, resulting in low filling and reduced battery efficiency. If the proportion of the polyolefin-thiol system is too high, the curing speed is fast, the viscosity increases, and it is easy to hang on the edge during dissociation, resulting in residues, affecting light incidence and current, resulting in reduced battery performance.
[0127] It can be seen from Example 1 and Example 8 that if unsaturated polyester is not added to the UV glue, there is no active diluent in the UV glue, which makes the degree of curing uneven. The uneven substrate during coating leads to reduced uniformity of the perovskite film layer, making the filling efficiency low.
[0128] It can be seen from Example 1 and Comparative Example 1 that if step (1) is performed and the UV glue in step (2) is replaced with double-sided tape, and a protective film made of a polymer material is provided on the surface of one side where the flexible substrate and the glass substrate are adhered, the double-sided tape may lose its adhesiveness during annealing and crystallization, and there is a risk of falling off. When the polymer protective film leaves, some residues will be left on the light incident surface, causing the refractive index of the light incident surface film to increase, resulting in lower current and lower efficiency.
[0129] It can be seen from Example 1 and Comparative Example 2 that if the polyolefin-thiol system is not added to the UV glue described in step (1), the hardness of the glue will become lower. During the coating process of perovskite, too low hardness will lead to uneven coating, resulting in poor film uniformity, low fill factor, and decreased battery efficiency.
[0130] It can be seen from Example 1 and Comparative Example 3 that, compared with the perovskite solar cell made on rigid glass, the flexible perovskite solar cell provided by the present invention has similar efficiency, indicating that the flexible perovskite solar cell has a bright development prospect.
[0131] The applicant declares that the present invention illustrates the process method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned process steps, that is, it does not mean that the present invention must rely on the above-mentioned process steps to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of the raw materials selected by the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.
Claims
1. A method for preparing a large-area flexible perovskite solar cell, characterized in that: The preparation method comprises the following steps: (1) coating UV glue on one side surface of the flexible substrate, and then attaching the flexible substrate to the rigid substrate by means of UV glue; (2) depositing a conductive layer, a first charge transport layer, a perovskite layer, a second charge transport layer and an electrode layer in sequence on a surface of the flexible substrate away from the rigid substrate; (3) photolyzing the UV glue and providing a layer of polymer film on the electrode layer, so that the polymer film and the flexible substrate are bonded to each other on all sides, and then performing sealing hot melting to complete the packaging, thereby obtaining the large-area flexible perovskite solar cell; Wherein, the UV glue comprises polyester organic matter, epoxy acrylate, polyolefin-thiol system and photoinitiator.
2. The preparation method according to claim 1, characterized in that: The UV glue comprises the following components in percentage by mass: 45-55% polyester organic matter, 5-15% polyolefin-thiol system, 2-10% photoinitiator, and the balance is epoxy acrylate.
3. The preparation method according to claim 1 or 2, characterized in that: The polyester organic matter includes any one of unsaturated polyester, polyacrylate or polyurethane acrylate or a combination of at least two thereof, preferably a combination of unsaturated polyester, polyacrylate and polyurethane acrylate; Preferably, based on the mass of the polyester organic matter, the mass fraction of the unsaturated polyester is 10-50%, the mass fraction of the polyacrylate is 20-60%, and the mass fraction of the polyurethane acrylate is 10-40%; Preferably, the photoinitiator includes any one of benzoin derivatives, dibenzoyl derivatives, α-carboxy ketone compounds, α-amino ketone compounds, phosphine oxide compounds, benzophenone or thioxanthone, or a combination of at least two thereof.
4. The preparation method according to any one of claims 1 to 3, characterized in that The coating method in step (1) includes slit coating or spin coating; Preferably, the material of the flexible substrate in step (1) includes any one of PET, PEN or PI; Preferably, the rigid substrate in step (1) comprises a glass substrate.
5. The preparation method according to any one of claims 1 to 4, characterized in that: The conductive layer in step (2) comprises a FTO layer; Preferably, in step (2), the charges transported by the first charge transport layer and the second charge transport layer are of opposite electrical properties; Preferably, in step (2), the first charge transport layer is a hole transport layer, and the hole transport layer comprises a nickel oxide layer; Step (2) The second charge transport layer is an electron transport layer, and the electron transport layer includes a tin oxide layer and / or a C 60 layer; Preferably, the perovskite layer in step (2) comprises any one of an organic perovskite layer, an organic-inorganic hybrid perovskite layer or an inorganic perovskite layer; Preferably, the electrode layer in step (2) is a metal electrode layer; Preferably, the material of the polymer film in step (3) is the same as the material of the flexible substrate.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The specific steps of sequentially depositing the conductive layer, the first charge transport layer, the perovskite layer, the second charge transport layer and the electrode layer in step (2) include: (a) depositing a conductive layer on a surface of the flexible substrate away from the rigid substrate, and then performing a first laser scribing on a surface of the conductive layer away from the flexible substrate to form a plurality of evenly spaced first scribing grooves; wherein the conductive layer is removed in the first scribing grooves; (b) depositing a first charge transport layer, a perovskite layer, and a second charge transport layer in sequence on the surface of the conductive layer after the first laser scribing, and then performing a second laser scribing on a surface of the second charge transport layer away from the flexible substrate to form a plurality of evenly spaced second grooves; wherein the first charge transport layer, the perovskite layer, and the second charge transport layer are removed in the second grooves, and the second grooves are located on one side of the first grooves and are spaced apart from the first grooves; (c) depositing an electrode layer on the surface of the second charge transport layer after the second laser scribing, and then performing a third laser scribing on the surface of the electrode layer away from the flexible substrate to form a plurality of evenly spaced third grooves; wherein the first charge transport layer, the perovskite layer, the second charge transport layer and the electrode layer are removed in the third grooves, the third grooves are located on one side of the second grooves and are spaced apart from the second grooves, and the second grooves are located between the first grooves and the third grooves.
7. The preparation method according to any one of claims 1 to 6, characterized in that: The specific steps of the sealed hot melt in step (3) include: First, the polymer film and the flexible substrate are heat-fused in three directions after being bonded around each other. Then, the openings that have not been heat-fused are vacuumed, inert gas is passed, and vacuumed again in sequence, and then the openings are heat-fused.
8. The preparation method according to any one of claims 1 to 7, characterized in that: The preparation method comprises the following steps: (1) Preparation of UV glue: The UV glue is obtained by mixing polyacrylate, polyurethane acrylate, unsaturated polyester, epoxy acrylate, polyolefin-thiol system and photoinitiator; wherein the total proportion of polyacrylate, polyurethane acrylate and unsaturated polyester is 45-55%, the proportion of polyolefin-thiol system is 5-15%, the proportion of photoinitiator is 2-10%, and the balance is epoxy acrylate; (2) coating UV glue on one side of the flexible substrate by a slit coating method, and then attaching the flexible substrate to the glass substrate by means of UV glue; (3) depositing an FTO layer on a surface of the flexible substrate away from the rigid substrate, and then performing a first laser scribing on a surface of the FTO layer away from the flexible substrate to form a plurality of evenly spaced first grooves; wherein the FTO layer is removed in the first grooves; the first laser scribing uses a laser with a wavelength of 1064 nm, and the laser is incident perpendicular to the surface of the FTO layer; and the interval between adjacent first grooves is 25-35 μm; (4) depositing a hole transport layer with a thickness of 15-25 nm, a perovskite layer with a thickness of 500-600 nm, and an electron transport layer with a thickness of 30-40 nm on the surface of the FTO layer after the first laser scribing, and then performing a second laser scribing on the surface of the electron transport layer away from the flexible substrate to form a plurality of evenly spaced second grooves; wherein the hole transport layer, the perovskite layer, and the electron transport layer are removed in the second grooves, the second grooves are located on one side of the first grooves, and there is a gap between the second grooves and the first grooves; the second laser scribing uses a laser with a wavelength of 532 nm, and the laser is incident perpendicular to the surface of the electron transport layer; the interval between adjacent second grooves is 45-55 μm, and the interval between the second grooves and the first grooves is 10-20 μm; (5) depositing a metal electrode layer with a thickness of 80-120 nm on the surface of the electron transport layer after the second laser scribing, and then performing a third laser scribing on the surface of the metal electrode layer away from the flexible substrate to form a plurality of evenly spaced third grooves; wherein the hole transport layer, the perovskite layer, the electron transport layer and the metal electrode layer are removed in the third grooves, the third grooves are located on one side of the second grooves, and there is a gap between the third grooves and the second grooves, and the second grooves are located between the first grooves and the third grooves; the third laser scribing uses a laser with a wavelength of 355 nm, and the laser is incident perpendicular to the surface of the metal electrode layer; the interval between adjacent third grooves is 35-45 μm, and the interval between the second grooves and the third grooves is 25-35 μm; (6) Using a UV decomposition machine, the UV glue is photolyzed to make the UV glue lose its stickiness and separate from the flexible substrate. Then, a layer of polymer film is disposed on the metal electrode layer, so that the polymer film and the flexible substrate are bonded to each other on all sides, and then sealed by hot melting. That is, the polymer film and the flexible substrate are first hot melted in three directions after being bonded to each other on all sides. Then, vacuuming, passing inert gas, and vacuuming are performed in sequence through the opening that has not been hot melted. Subsequently, the opening is hot melted and sealed to complete the packaging, thereby obtaining the large-area flexible perovskite solar cell.
9. A large-area flexible perovskite solar cell, characterized in that: The large-area flexible perovskite solar cell is prepared by the preparation method according to any one of claims 1 to 8.
10. A photovoltaic module, characterized in that: The photovoltaic module includes the large-area flexible perovskite solar cell as described in claim 9.
Citation Information
Cited By
Portable perovskite photovoltaic coiled material and preparation method and application thereof
CN120379447A
